A carbon fiber paper and a method for manufacturing the same
Patent Information
- Application Number
- CN202410869831.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-01
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-07-01
AI Technical Summary
[0005]本申请提供一种碳纤维纸及其制备方法,旨在解决现有技术中难以同时兼顾制备成本以及碳纤维纸各性能达到平衡的问题
[0016]本申请技术方案,提出一种碳纤维纸及其制备方法。该制备方法包括步骤:a)将碳纤维放入氢氧化钠溶液中浸渍处理,而后洗涤过滤,干燥得到预处理碳纤维;b)将预处理碳纤维浸没于多巴胺溶液中,浸渍完成后经洗涤得到改性碳纤维;c)将改性碳纤维与聚乙烯醇纤维按预设质量配比,并配制得到混合浆料;d)稀释混合浆料达到上网浓度,基于稀释后的混合浆料进行抄纸作业,压榨脱水,经干燥后得到纸页前驱体;e)在纸页前驱体的表面涂布导电涂料,再经干燥、压光和卷曲后获得碳纤维纸。本申请技术方案通过以上制备步骤制备碳纤维纸,其中,在步骤a)中氢氧化钠浸渍能够增加碳纤维表面含氧官能团,促进碳纤维在后续步骤中与多巴胺的结合,同时增加了碳纤维表面羧基和羟基,提高了分散性能;在步骤b)中,多巴胺氧化自聚合在碳纤维上,对碳纤维进行氧化,提高了碳纤维与多巴胺的化学结合力,同时增加碳纤维之间结合力。在步骤c)中,添加聚乙烯醇纤维与改性碳纤维共同制备混合浆料;而后通过步骤d)制备得到纸页前驱体,在干燥过程中,聚乙烯醇纤维可熔融以增加碳纤维之间的结合力;在步骤e)中,通过在涂布导电涂料,干燥、压光和卷曲后获得碳纤维纸,导电涂料能够进一步提高碳纤维纸的导电性能以及纤维之间的结合强度。进而,本申请技术方案通过简单的步骤,可以较低的成本制备获得碳纤维纸,且该碳纤维纸具有抗张强度大、孔径小、孔隙率和导电性能好的优异性能。
Smart Images

Figure CN118814521B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of papermaking technology, and in particular to a carbon fiber paper and its preparation method. Background Technology
[0002] With the development of a low-carbon economy, hydrogen energy has become one of the most promising energy sources. As one of the most important hydrogen energy conversion devices, proton exchange membrane fuel cells (PEMFCs) have attracted widespread attention. PEMFCs offer advantages such as low operating temperature, fast start-up speed, long service life, modular installation, and ease of operation, making them ideal candidate power sources for a range of stationary and mobile applications, such as electric vehicles, mobile devices, and distributed power plants. PEMFCs belong to the fourth generation of fuel cells, with an electrolyte made of a polymeric proton exchange membrane, and electrodes consisting of a gas diffusion layer and a catalyst layer.
[0003] High-performance carbon fiber paper is the most commonly used substrate material for gas diffusion layers, meeting the operating conditions and performance requirements of fuel cells. Existing technologies offer various preparation methods for carbon fiber paper. For example, using carbon fiber paper with a gradient structure, while providing better water conductivity, mechanical properties, and electrical conductivity, results in a relatively complex preparation process, thicker paper, and poor interlayer bonding. Alternatively, adding reinforcing fibers and constructing organometallic framework compounds on the carbon fiber paper surface effectively solves the problems of poor electrical conductivity and low mechanical strength in existing carbon fiber paper, but the smooth carbon fiber surface and poor dispersion properties fail to effectively improve the unevenness of the carbon fiber paper. Another method involves adding aramid fibers to the carbon fiber paper, which effectively improves the structural uniformity and strength, but the cost is relatively high, and the paper thickness is large.
[0004] Therefore, due to limitations in the existing manufacturing process, it is difficult to simultaneously balance manufacturing costs and the various properties of carbon fiber paper. It is necessary to improve the existing manufacturing process of carbon fiber paper. Summary of the Invention
[0005] This application provides a carbon fiber paper and its preparation method, aiming to solve the problem in the prior art that it is difficult to simultaneously balance the preparation cost and the various properties of carbon fiber paper.
[0006] To achieve the above objectives, this application proposes a method for preparing carbon fiber paper, which includes the following steps: a) The carbon fiber is immersed in sodium hydroxide solution, then washed, filtered, and dried to obtain pretreated carbon fiber; b) The pretreated carbon fiber is immersed in a dopamine solution, and after impregnation, it is washed to obtain modified carbon fiber; c) The modified carbon fiber and polyvinyl alcohol fiber are mixed in a preset mass ratio to prepare a mixed slurry; d) Dilute the mixed pulp to the required online concentration, perform papermaking operations based on the diluted mixed pulp, press and dewater, and dry to obtain the paper precursor; e) A conductive coating is applied to the surface of the paper precursor, and then dried, calendered and rolled to obtain carbon fiber paper.
[0007] In some embodiments, in step a), the concentration of sodium hydroxide is 10% to 20%, and the immersion treatment time is 0.5 to 3 hours; The carbon fiber has a fiber length of 3 to 10 mm and a fiber diameter of 4 to 10 μm.
[0008] In some embodiments, step b) further includes preparing a dopamine solution before immersing the pretreated carbon fiber in the dopamine solution, the preparation process of the dopamine solution including; Dissolve 1 part of tris(hydroxymethyl)aminomethane in 1000 parts of water by mass percentage to obtain a mixed solution; Add hydrochloric acid to the mixed solution until pH=8.5 to prepare a buffer solution; Dopamine powder was added to the buffer solution and stirred until homogeneous to obtain the dopamine solution.
[0009] In some embodiments, the concentration of the dopamine solution is 2 to 8 g / L, and the pretreated carbon fiber is impregnated in the dopamine solution for no less than 24 hours.
[0010] In some embodiments, in step c), the preset mass, by mass percentage, comprises 80% to 95% modified carbon fiber and 5% to 20% polyvinyl alcohol fiber.
[0011] In some embodiments, the length of the polyvinyl alcohol fiber is 5 to 10 mm.
[0012] In some embodiments, in step d), the mixed slurry is diluted with white water, and the online concentration is 0.02%~0.05%; the drying temperature is 100℃~140℃.
[0013] In some embodiments, in step e), the concentration of the conductive coating is 10% to 20%, and the coating amount on the surface of the paper precursor is 1 to 2 g / m². 2 .
[0014] In some embodiments, the conductive coating comprises, by weight: 85-95 parts conductive particles, 5-10 parts adhesive, 0.5 parts dispersant, and 0.3 parts defoamer; Wherein, the conductive particles are one or more of carbon nanotubes, conductive carbon black, and graphene; the adhesive is one or more of polyvinyl alcohol, starch, and styrene-butadiene latex; the dispersant is sodium acrylate and / or sodium hexametaphosphate; and the defoamer is an organosilicone defoamer.
[0015] This application also provides a carbon fiber paper, which is prepared by the carbon fiber paper preparation method described above.
[0016] This application proposes a carbon fiber paper and its preparation method. The preparation method includes the following steps: a) immersing carbon fibers in a sodium hydroxide solution, then washing, filtering, and drying to obtain pretreated carbon fibers; b) immersing the pretreated carbon fibers in a dopamine solution, and washing after immersion to obtain modified carbon fibers; c) mixing the modified carbon fibers and polyvinyl alcohol fibers according to a preset mass ratio to prepare a mixed slurry; d) diluting the mixed slurry to reach the required online concentration, performing papermaking operations based on the diluted mixed slurry, pressing and dewatering, and drying to obtain a paper precursor; e) coating the surface of the paper precursor with a conductive coating, and then drying, calendering, and curling to obtain carbon fiber paper. This application's technical solution prepares carbon fiber paper through the above preparation steps. In step a), sodium hydroxide impregnation increases the oxygen-containing functional groups on the carbon fiber surface, promoting the binding of carbon fibers with dopamine in subsequent steps. It also increases the carboxyl and hydroxyl groups on the carbon fiber surface, improving dispersion performance. In step b), dopamine oxidizes and self-polymerizes on the carbon fibers, oxidizing them and increasing the chemical bonding force between carbon fibers and dopamine, while also increasing the bonding force between carbon fibers. In step c), polyvinyl alcohol fibers are added to prepare a mixed slurry with modified carbon fibers. Then, in step d), a paper precursor is prepared. During drying, the polyvinyl alcohol fibers can melt to increase the bonding force between carbon fibers. In step e), carbon fiber paper is obtained by coating with a conductive coating, drying, calendering, and curling. The conductive coating further improves the conductivity of the carbon fiber paper and the bonding strength between fibers. Therefore, this application's technical solution can prepare carbon fiber paper at a low cost through simple steps, and this carbon fiber paper possesses excellent properties such as high tensile strength, small pore size, low porosity, and good conductivity. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort, wherein: Figure 1 This is a schematic flowchart of a method for preparing carbon fiber paper according to an embodiment of this application. Detailed Implementation
[0018] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0019] See Figure 1 As shown, this application proposes a method for preparing carbon fiber paper. The preparation method includes the following steps: a) The carbon fiber is immersed in sodium hydroxide solution, then washed, filtered, and dried to obtain pretreated carbon fiber.
[0020] The main purpose of this process is to modify the surface properties of carbon fibers through chemical methods, particularly by increasing the number of oxygen-containing functional groups on their surface, thereby improving their bonding ability and dispersion properties with other materials (such as dopamine).
[0021] Understandably, carbon fibers are primarily composed of carbon, and their surface is typically nonpolar, making them less able to bind to many polar substances (such as dopamine). Sodium hydroxide solution is a strong base that can react with certain groups on the carbon fiber surface, introducing oxygen-containing functional groups such as hydroxyl (-OH) and carboxyl (-COOH). These functional groups can enhance the polarity of the carbon fiber surface, improving its binding ability to polar substances like dopamine. Simultaneously, they can form hydrogen bonds with water or other polar solvents, making the carbon fibers easier to disperse in solution.
[0022] The sodium hydroxide solution concentration is 10%–20%. Lower concentrations (e.g., 5%) primarily serve as surface cleaners, removing non-reactive impurities from the carbon fiber surface and introducing oxygen-containing functional groups. However, as the concentration increases, the alkalinity of sodium hydroxide strengthens, leading to a more vigorous reaction with the carbon fiber surface and more efficient introduction of oxygen-containing functional groups such as hydroxyl and carboxyl groups. Immersing the carbon fiber in this concentration of sodium hydroxide solution for 0.5–3 hours further enhances the reaction, resulting in more oxygen-containing functional groups on the carbon fiber surface and significantly improving its surface properties.
[0023] When selecting carbon fibers, those with a fiber length of 3–10 mm and a fiber diameter of 4–10 μm are preferred. The length and diameter of the carbon fiber determine its mechanical properties and structural characteristics. Longer fiber length generally means higher strength and better structural integrity, as longer fibers are better able to resist breakage and damage under external forces; while a smaller fiber diameter helps increase the specific surface area of the carbon fiber, thereby improving its contact area and bonding strength with other materials. Therefore, carbon fibers within this parameter range are more suitable for preparing the carbon fiber paper of this application.
[0024] After the carbon fiber is impregnated in sodium hydroxide solution, it is washed and filtered to ensure the cleanliness and purity of the carbon fiber surface. Then, it is dried to remove surface moisture, bringing it to a suitable dry state for subsequent processing. Typically, pure water or anhydrous ethanol is used for washing.
[0025] b) The pretreated carbon fiber was immersed in a dopamine solution, and after impregnation, it was washed to obtain modified carbon fiber.
[0026] This step is to modify the surface of carbon fibers through the chemical action of dopamine.
[0027] Dopamine, as a biomolecule, possesses abundant functional groups such as amino and hydroxyl groups. It can react with oxygen-containing functional groups (such as hydroxyl and carboxyl groups) on the surface of carbon fibers, thereby forming a dopamine coating on the carbon fiber surface. This dopamine coating can improve the surface properties of carbon fibers, such as enhancing their wettability, adhesion, and chemical stability, thereby increasing the bonding force between carbon fibers.
[0028] The concentration and impregnation time of the dopamine solution have a significant impact on the modification effect. In this application, the pretreated carbon fibers are immersed in a dopamine solution with a concentration of 2-8 g / L for no less than 24 hours to ensure the deposition of dopamine on the carbon fiber surface, thereby enhancing the modification effect. At the same time, it prevents the formation of an excessively thick coating on the carbon fiber surface by dopamine, which would affect its mechanical properties and surface morphology.
[0029] The concentration of the dopamine solution and the impregnation time can be adjusted according to specific application requirements. After impregnation, washing is performed to ensure that free dopamine molecules that are not bound to the carbon fiber are completely removed, so as to avoid negative impact on the performance of the carbon fiber.
[0030] It is worth noting that the process of preparing the dopamine solution before immersing the pretreated carbon fibers in a dopamine solution with a concentration of 2-8 g / L includes the preparation of the dopamine solution. Dissolve 1 part of tris(hydroxymethyl)aminomethane in 1000 parts of water by mass percentage to obtain a mixed solution; add hydrochloric acid to the mixed solution until pH=8.5 to prepare a buffer solution; add 2-8 g of dopamine powder to each 1 L of buffer solution and stir well to obtain a dopamine solution.
[0031] During the preparation of the mixed solution, it is important to pay attention to the mass ratio of tris(hydroxymethyl)aminomethane to water. For example, 1g of tris(hydroxymethyl)aminomethane requires 1000ml of water. Add hydrochloric acid to the mixed solution while continuously stirring and monitoring the pH value until it reaches 8.5. pH adjustment is crucial for the stability of dopamine and the final performance of the solution. Add 2-8g of dopamine powder to every 1L (1000ml) of pH-adjusted buffer solution, stirring thoroughly to ensure the dopamine powder is completely dissolved. Stirring can be achieved using a magnetic stirrer or manually.
[0032] c) The modified carbon fiber and polyvinyl alcohol fiber are mixed in a preset mass ratio to prepare a mixed slurry.
[0033] The polyvinyl alcohol fiber used begins to melt at 90°C. After adding this polyvinyl alcohol fiber, the polyvinyl alcohol fiber will melt during the subsequent high-temperature drying process, thereby increasing the bonding force between the carbon fibers.
[0034] In this step, the mass ratio of modified carbon fiber to polyvinyl alcohol fiber is determined according to specific application needs or design requirements.
[0035] This ratio can be adjusted according to the desired performance. For example, if higher strength and stiffness are required, the proportion of modified carbon fiber can be increased; if better flexibility and processability are required, the proportion of PVA fiber can be increased. Furthermore, the dopamine added in step b) can improve the bonding strength between the modified carbon fiber and the polyvinyl alcohol fiber. Preferably, the preset mass percentage is 80%–95% modified carbon fiber and 5%–20% polyvinyl alcohol fiber.
[0036] Then, the required mass of modified carbon fiber and polyvinyl alcohol fiber are weighed separately, and two trough pulpers are used to decompose the modified carbon fiber and polyvinyl alcohol fiber respectively. Then, the pulp is put into the mixing tank to prepare mixed pulp for papermaking.
[0037] The polyvinyl alcohol fibers are 5–10 mm in length. Fibers in this length range provide good mechanical properties and stability in the mixed slurry.
[0038] d) Papermaking is performed based on the diluted mixed pulp, followed by pressing and dewatering, and then drying to obtain a paper precursor.
[0039] In this step, a wire mesh paper machine can be used for papermaking. In the manufacturing process of long fiber specialty paper, wire mesh forming has obvious advantages over other paper machines such as wire mesh in the production of certain specialty papers due to its good dewatering performance, papermaking uniformity, good air permeability, low wire mesh concentration, and the ability to form long fibers.
[0040] Furthermore, this inclined wire paper machine is a single-forming wire with floating blades. The single-forming wire with floating blades has a novel structure, being a closed inclined wire (hydraulic type), which can effectively mix carbon fibers and polyvinyl alcohol fibers with different specific gravities, further improving the uniformity of carbon fiber paper.
[0041] To ensure excellent fiber dispersion, the online concentration of the mixed pulp is diluted with white water. White water is a large amount of water discharged from the wire section of the paper machine during papermaking, containing fine and short fibers and other substances added to the pulp. Preferably, the online concentration is 0.02% to 0.05%; the lower the online concentration, the better the fiber dispersion.
[0042] After papermaking, further pressing and dewatering are required, followed by drying to obtain the paper precursor. The pressing device consists of a double-blanket press section. More preferably, a regular positive press is performed after the double-blanket press to reduce the difference in smoothness between the two sides of the carbon fiber paper. The drying temperature is 100℃~140℃, so that the polyvinyl alcohol fibers begin to melt at 90℃. The molten polyvinyl alcohol fibers increase the bonding force between the carbon fibers.
[0043] e) A conductive coating is applied to the surface of the paper precursor, and then dried, calendered and rolled to obtain carbon fiber paper.
[0044] In this step, the surface coating of the paper precursor with conductive coating material is a key step in the preparation of carbon fiber paper. The conductive coating can be applied using the sizing section of a slanted wire paper machine. The conductive coating is uniformly applied to the surface of the paper precursor to improve the conductivity of the carbon fiber paper.
[0045] The conductive coating has a coating concentration of 10%–20%, and the coating amount on the surface of the paper precursor is 1–2 g / m². 2 The coating amount of conductive coating directly affects the conductivity of carbon fiber paper. Within the range of 1–2 g / m², conductive particles can form a continuous and uniform conductive network on the paper surface, thus ensuring good conductivity of the carbon fiber paper. This also ensures a balance between conductivity and mechanical properties.
[0046] The conductive coating comprises, by weight, 85-95 parts conductive particles, 5-10 parts adhesive, 0.5 parts dispersant and 0.3 parts defoamer.
[0047] Conductive particles are a major component of conductive coatings, responsible for providing the coating's conductivity. Conductive particles include one or more of carbon nanotubes, conductive carbon black, and graphene. Generally, a higher content of conductive particles results in better conductivity, but it can also affect the coating's coatability and mechanical properties. Therefore, selecting an appropriate conductive particle content within the range of 85–95 parts per part is crucial for balancing conductivity and other properties.
[0048] Adhesives are used to firmly adhere conductive particles to the surface of the paper precursor, forming a uniform conductive coating. The adhesive is one or more of polyvinyl alcohol, starch, and styrene-butadiene latex. Insufficient adhesive may lead to poor coating adhesion and easy peeling; excessive adhesive may reduce the coating's conductivity. Therefore, selecting an appropriate adhesive content within the range of 5 to 10 parts ensures good adhesion and conductivity of the coating.
[0049] The role of dispersants is to help conductive particles disperse evenly in coatings, preventing particle agglomeration and sedimentation. An appropriate amount of dispersant can improve the stability and application performance of the coating. A dosage of 0.5 parts dispersant is usually sufficient for this purpose.
[0050] Defoamers are used to eliminate air bubbles generated during the mixing and application of coatings, preventing these bubbles from affecting the quality and performance of the coating. A dosage of 0.3 parts defoamer is usually sufficient to effectively control bubble formation.
[0051] After coating, carbon fiber paper is obtained through drying, calendering, and curling. Drying removes moisture and solvents from the coating, allowing the conductive coating to solidify on the paper surface. Drying can be done by air drying or heat drying. Calendering improves the smoothness and gloss of the paper, making its surface more uniform and smooth. Calendering can be done by mechanical calendering or hot calendering. Finally, the paper needs to be curled to form a roll of carbon fiber paper.
[0052] This application prepares carbon fiber paper using the above-described preparation method, achieving cost reduction while maintaining excellent physical properties. Specific embodiments of the carbon fiber paper are presented below based on the above preparation method. It should be understood that the specific embodiments presented below are only partial embodiments based on the above technical solution, with variations in material selection and parameter settings. In some other specific embodiments, materials can be freely combined and parameters set within the scope of the technical solution claimed in this application to prepare the carbon fiber paper of this application. After obtaining the carbon fiber paper in each embodiment, various properties of the carbon fiber paper are tested, including: Refer to GB / T451.3-2002 and use a computer-controlled thickness and density tester to measure the thickness of carbon fiber paper.
[0053] Carbon fiber paper was prepared into thin strips with a width of 1.5 cm. Test specimens were selected according to GB / T 12914-2018 standard. The specimens were fixed on a tensile testing machine, and a tensile strength test was conducted after setting the specified test speed. The tensile strength of the paper was calculated using the formula:
[0054] In the formula, S is the tensile strength of the paper sample, with units of kN·m. -1 F represents the tensile strength of the paper sample, in N; L w This refers to the cross-sectional area of the paper pattern, in mm. 2 .
[0055] The porosity and pore size of paper samples were determined using a high-performance fully automated mercury porosimeter.
[0056] The sample was cut into squares with sides of 1.5 cm, and its mass and thickness were measured and recorded. The current after the sample stabilized was measured using a digital source meter. It was ensured that the pressure applied to the sample contact points was consistent throughout the measurement process, and the airflow was reduced to ensure the sample remained stationary during the measurement. The resistivity of the sample was calculated using the following formula:
[0057] In the formula, ρ is the resistivity of the paper sample, in mΩ·cm; R is the resistance of the paper sample, in mΩ; and S is the cross-sectional area of the paper sample, in cm². 2 L represents the distance between contact points, in cm.
[0058] Example 1 a) The carbon fiber was immersed in a 15% sodium hydroxide solution for 2 hours. After immersion, it was thoroughly filtered and washed with anhydrous ethanol. The washed carbon fiber was then vacuum dried to obtain pretreated carbon fiber.
[0059] b) Prepare a dopamine solution with a concentration of 2 g / L. Completely immerse the carbon fibers in the dopamine solution, and wash the fibers thoroughly with water after 24 hours.
[0060] c) Prepare a mixed slurry by mixing 80 parts of modified carbon fiber and 20 parts of polyvinyl alcohol fiber by mass percentage.
[0061] d) A paper precursor was prepared based on the diluted mixed pulp to achieve a net concentration of 0.04% by dilution with white water.
[0062] e) A conductive coating is applied to the surface of a paper precursor, and carbon fiber paper is obtained after drying, calendering and curling. The conductive coating comprises the following components by weight: 89.2 parts conductive particles, 10 parts adhesive, 0.5 parts dispersant and 0.3 parts defoamer.
[0063] The performance data of the carbon fiber paper prepared in this embodiment are shown in Table 1: Table 1
[0064] Example 2 a) The carbon fiber was immersed in a 15% sodium hydroxide solution for 2 hours. After immersion, it was thoroughly filtered and washed with anhydrous ethanol. The washed carbon fiber was then vacuum dried to obtain pretreated carbon fiber.
[0065] b) Prepare a dopamine solution with a concentration of 4 g / L. Completely immerse the carbon fibers in the dopamine solution. After 24 hours, thoroughly wash the fibers with water.
[0066] c) Prepare a mixed slurry by mixing 80 parts of modified carbon fiber and 20 parts of polyvinyl alcohol fiber by mass percentage.
[0067] d) A paper precursor was prepared based on the diluted mixed pulp to achieve a net concentration of 0.04% by dilution with white water.
[0068] e) A conductive coating is applied to the surface of a paper precursor, and carbon fiber paper is obtained after drying, calendering and curling. The conductive coating comprises the following components by weight: 89.2 parts conductive particles, 10 parts adhesive, 0.5 parts dispersant and 0.3 parts defoamer.
[0069] The performance data of the carbon fiber paper prepared in this embodiment are shown in Table 2: Table 2
[0070] Example 3 a) The carbon fiber was immersed in a 15% sodium hydroxide solution for 2 hours. After immersion, it was thoroughly filtered and washed with anhydrous ethanol. The washed carbon fiber was then vacuum dried to obtain pretreated carbon fiber.
[0071] b) Prepare a dopamine solution with a concentration of 6 g / L. Completely immerse the carbon fibers in the dopamine solution. After 24 hours, thoroughly wash the fibers with water.
[0072] c) Prepare a mixed slurry by mixing 80 parts of modified carbon fiber and 20 parts of polyvinyl alcohol fiber by mass percentage.
[0073] d) A paper precursor was prepared based on the diluted mixed pulp to achieve a net concentration of 0.04% by dilution with white water.
[0074] e) A conductive coating is applied to the surface of a paper precursor, and carbon fiber paper is obtained after drying, calendering and curling. The conductive coating comprises the following components by weight: 89.2 parts conductive particles, 10 parts adhesive, 0.5 parts dispersant and 0.3 parts defoamer.
[0075] The performance data of the carbon fiber paper prepared in this embodiment are shown in Table 3: Table 3
[0076] Example 4 a) The carbon fiber was immersed in a 15% sodium hydroxide solution for 2 hours. After immersion, it was thoroughly filtered and washed with anhydrous ethanol. The washed carbon fiber was then vacuum dried to obtain pretreated carbon fiber.
[0077] b) Prepare a dopamine solution with a concentration of 8 g / L. Completely immerse the carbon fibers in the dopamine solution. After 24 hours, thoroughly wash the fibers with water.
[0078] c) Prepare a mixed slurry by mixing 80 parts of modified carbon fiber and 20 parts of polyvinyl alcohol fiber by mass percentage.
[0079] d) A paper precursor was prepared based on the diluted mixed pulp to achieve a net concentration of 0.04% by dilution with white water.
[0080] e) A conductive coating is applied to the surface of a paper precursor, and carbon fiber paper is obtained after drying, calendering and curling. The conductive coating comprises the following components by weight: 89.2 parts conductive particles, 10 parts adhesive, 0.5 parts dispersant and 0.3 parts defoamer.
[0081] The performance data of the carbon fiber paper prepared in this embodiment are shown in Table 4: Table 4
[0082] Example 5 a) The carbon fiber was immersed in a 15% sodium hydroxide solution for 2 hours. After immersion, it was thoroughly filtered and washed with anhydrous ethanol. The washed carbon fiber was then vacuum dried to obtain pretreated carbon fiber.
[0083] b) Prepare a dopamine solution with a concentration of 2 g / L. Completely immerse the carbon fibers in the dopamine solution, and wash the fibers thoroughly with water after 24 hours.
[0084] c) Prepare a mixed slurry by mixing 90 parts of modified carbon fiber and 10 parts of polyvinyl alcohol fiber by mass percentage.
[0085] d) A paper precursor was prepared based on the diluted mixed pulp to achieve a net concentration of 0.04% by dilution with white water.
[0086] e) A conductive coating is applied to the surface of a paper precursor, and carbon fiber paper is obtained after drying, calendering and curling. The conductive coating comprises the following components by weight: 89.2 parts conductive particles, 10 parts adhesive, 0.5 parts dispersant and 0.3 parts defoamer.
[0087] The performance data of the carbon fiber paper prepared in this embodiment are shown in Table 5: Table 5
[0088] Example 6 a) The carbon fiber was immersed in a 15% sodium hydroxide solution for 2 hours. After immersion, it was thoroughly filtered and washed with anhydrous ethanol. The washed carbon fiber was then vacuum dried to obtain pretreated carbon fiber.
[0089] b) Prepare a dopamine solution with a concentration of 2 g / L. Completely immerse the carbon fibers in the dopamine solution, and wash the fibers thoroughly with water after 24 hours.
[0090] c) Prepare a mixed slurry by mixing 95 parts of modified carbon fiber and 5 parts of polyvinyl alcohol fiber by mass percentage.
[0091] d) A paper precursor was prepared based on the diluted mixed pulp to achieve a net concentration of 0.04% by dilution with white water.
[0092] e) A conductive coating is applied to the surface of a paper precursor, and carbon fiber paper is obtained after drying, calendering and curling. The conductive coating comprises the following components by weight: 89.2 parts conductive particles, 10 parts adhesive, 0.5 parts dispersant and 0.3 parts defoamer.
[0093] The performance data of the carbon fiber paper prepared in this embodiment are shown in Table 6: Table 6
[0094] Example 7 a) The carbon fiber was immersed in a 15% sodium hydroxide solution for 2 hours. After immersion, it was thoroughly filtered and washed with anhydrous ethanol. The washed carbon fiber was then vacuum dried to obtain pretreated carbon fiber.
[0095] b) Prepare a dopamine solution with a concentration of 2 g / L. Completely immerse the carbon fibers in the dopamine solution, and wash the fibers thoroughly with water after 24 hours.
[0096] c) Prepare a mixed slurry by mixing 80 parts of modified carbon fiber and 20 parts of polyvinyl alcohol fiber by mass percentage.
[0097] d) A paper precursor was prepared based on the diluted mixed pulp to achieve a net concentration of 0.04% by dilution with white water.
[0098] e) A conductive coating is applied to the surface of a paper precursor, and carbon fiber paper is obtained after drying, calendering and curling. The conductive coating comprises the following components by weight: 91.2 parts conductive particles, 8 parts adhesive, 0.5 parts dispersant and 0.3 parts defoamer.
[0099] The performance data of the carbon fiber paper prepared in this embodiment are shown in Table 7: Table 7
[0100] Example 8 a) The carbon fiber was immersed in a 15% sodium hydroxide solution for 2 hours. After immersion, it was thoroughly filtered and washed with anhydrous ethanol. The washed carbon fiber was then vacuum dried to obtain pretreated carbon fiber.
[0101] b) Prepare a dopamine solution with a concentration of 2 g / L. Completely immerse the carbon fibers in the dopamine solution, and wash the fibers thoroughly with water after 24 hours.
[0102] c) Prepare a mixed slurry by mixing 80 parts of modified carbon fiber and 20 parts of polyvinyl alcohol fiber by mass percentage.
[0103] d) A paper precursor was prepared based on the diluted mixed pulp to achieve a net concentration of 0.04% by dilution with white water.
[0104] e) A conductive coating is applied to the surface of a paper precursor, and carbon fiber paper is obtained after drying, calendering and curling. The conductive coating comprises the following components by weight: 94.2 parts conductive particles, 5 parts adhesive, 0.5 parts dispersant and 0.3 parts defoamer.
[0105] The performance data of the carbon fiber paper prepared in this embodiment are shown in Table 8: Table 8
[0106] As shown in Examples 1-4, the tensile strength of carbon fiber paper increases with increasing dopamine concentration. This is because the amount of polydopamine on the carbon fiber surface increases. Polydopamine molecules have hydrophilicity and adhesion capabilities, enabling them to form hydrogen bonds and van der Waals forces with polyvinyl alcohol molecules, thus strengthening the bond between the dopamine-modified carbon fiber and the polyvinyl alcohol matrix. Furthermore, the thickness and pore size decrease because with increasing dopamine concentration, the dopamine surface contains abundant hydrophilic functional groups, such as carboxyl, hydroxyl, and amino groups, further improving dispersion performance and resulting in denser carbon fiber weaving. However, dopamine itself is an organic compound and, under normal conditions, does not have high conductivity because it is an organic molecule whose molecular structure does not contain a large number of freely moving electrons. The resistivity also increases accordingly.
[0107] Examples 1, 5, and 6 show that as the amount of polyvinyl alcohol (PVA) fiber decreases, the thickness, porosity, and pore size of the carbon fiber paper increase. This is because the bonding between the dopamine-modified carbon fiber and the PVA matrix decreases, reducing the bonding force between the carbon fibers and preventing them from adhering tightly, thus increasing the thickness. The pore size between the fibers also increases, leading to an overall increase in porosity. Tensile strength and resistivity decrease because the PVA fiber melts during the drying process, increasing the bonding between the carbon fibers. While reducing the amount of PVA fiber decreases the bonding force between the carbon fibers, increasing the amount of carbon fiber reduces the resistivity.
[0108] As shown in Examples 1, 7, and 8, with the increase of the amount of conductive particles, the porosity, pore size, tensile strength, and resistivity of the carbon fiber paper decrease, while the thickness remains almost unchanged. This is because the conductive particles have a small particle size and fill the gaps between the fibers, reducing the pore size of the carbon fiber base paper and thus decreasing the overall porosity. However, the conductive particles have high conductivity, which can reduce the resistivity of the carbon fiber base paper.
[0109] In summary, the technical solution of this application, by impregnating pretreated carbon fibers in dopamine, adding polyvinyl alcohol fibers, and coating with conductive particles, can obtain carbon fiber paper with high tensile strength, small pore size, high porosity, and low resistivity.
[0110] The above description is only a part or preferred embodiment of this application. Neither the text nor the drawings should limit the scope of protection of this application. All equivalent structural transformations made using the content of this application's specification and drawings under the overall concept of this application, or direct / indirect applications in other related technical fields, are included within the scope of protection of this application.
Claims
1. A method for preparing carbon fiber paper, characterized in that, Carbon fiber paper is used in the preparation of a gas diffusion layer. The preparation method of the carbon fiber paper includes the following steps: a) The carbon fiber is immersed in a 10%–20% sodium hydroxide solution for 0.5–3 hours, then washed, filtered, and dried to obtain pretreated carbon fiber; the fiber length of the carbon fiber is 3–10 mm and the fiber diameter is 4–10 μm. b) The pretreated carbon fiber is immersed in a dopamine solution, and after impregnation, it is washed to obtain modified carbon fiber; The concentration of the dopamine solution is 2-8 g / L, and the pretreated carbon fiber is immersed in the dopamine solution for no less than 24 hours. c) The modified carbon fiber and polyvinyl alcohol fiber are mixed in a preset mass ratio to prepare a mixed slurry; the preset mass, by mass percentage, is 80% to 95% modified carbon fiber and 5% to 20% polyvinyl alcohol fiber; the length of the polyvinyl alcohol fiber is 5 to 10 mm. d) Dilute the mixed pulp to the required online concentration, perform papermaking operations based on the diluted mixed pulp, press and dewater, and dry to obtain a paper sheet precursor; the mixed pulp is diluted with white water, the online concentration is 0.02%~0.05%; the drying temperature is 100℃~140℃; e) A conductive coating is applied to the surface of the paper precursor, followed by drying, calendering, and curling to obtain carbon fiber paper; the concentration of the conductive coating is 10%–20%, and the coating amount on the surface of the paper precursor is 1–2 g / m². 2 ; The conductive coating comprises, by weight, 85-95 parts conductive particles, 5-10 parts adhesive, 0.5 parts dispersant, and 0.3 parts defoamer; wherein the conductive particles are one or more of carbon nanotubes, conductive carbon black, and graphene; the adhesive is one or more of polyvinyl alcohol, starch, and styrene-butadiene latex; the dispersant is sodium polyacrylate and / or sodium hexametaphosphate; the defoamer is an organosilicon defoamer; the carbon fiber paper has a thickness of 21-34 μm and a porosity of 74%-80%.
2. The method for preparing carbon fiber paper according to claim 1, characterized in that, In step b), before immersing the pretreated carbon fiber in the dopamine solution, the preparation of the dopamine solution is further included, the preparation process of the dopamine solution includes; Dissolve 1 part of tris(hydroxymethyl)aminomethane in 1000 parts of water by mass percentage to obtain a mixed solution; Add hydrochloric acid to the mixed solution until pH=8.5 to prepare a buffer solution; Dopamine powder was added to the buffer solution and stirred until homogeneous to obtain the dopamine solution.
3. A carbon fiber paper, characterized in that, The carbon fiber paper is prepared using the carbon fiber paper preparation method as described in claim 1 or 2.
Citation Information
Patent Citations
Composite material of modified carbon fibers and nanoaramid fibers and preparation method of composite material
CN108610628A
Preparation method of raw paper of carbon paper
CN116716755A
Proton exchange membrane fuel cell diffusion of gases layer carbon paper
CN207558942U
